Comparative evaluation of physico-morphological attributes and freezability of semen of Gir cattle (Bos indicus) and Jafarabadi buffalo (Bubalus bubalis) bulls - SHELKE, VINAY B; DHAMI, A J (The Indian Journal of Animal Sciences, 2014)
Semen ejaculates (99; 9 per bulls) obtained at 3-days interval from 6 Gir and 5 lafarabadi bulls; aged 4-7 years and of different freezability grades (good and poor); were evaluated for various physico-morphological attributes, freezability, cold shock resistance and their interrelationships. The mean values in Gir and lafara0.01 and 6.66 ± 0.02, mass activity 2.96 ± 0.14 and 2.23 ± 0.15 (P<0.01), initial motility 67.87 ± 2.69 and 59.44 ± 3.05% (P<0.05), sperm concentration 1219.44 ± 38.24 and 1209.56 ± 53.48 million/ml, live sperm 80.13 ± 1.43 and 82.60 ± 1.52%, total sperm abnormalities 15.54 ± 1.09 and 22.18 ± 3.11 % (P<0.05), crenellation score 2.07 ± 0.13 and 2.03 ± 0.11, cold shock resistant (live) sperm 38.19 ± 1.03 and 36.40 ± 1.23%, pre freeze motility 55.46 ± 2.80 and 41.65 ± 3.30% (P<0.01) and post-thaw motility 42.19 ± 2.67 and 28.22 ± 2.82% (P<0.01) respectively. Most of these traits were significantly (P<0.01) superior in good freezable than in poor freezable (2 bullsin each breed) group of bulls in both the species, and also varied significantly between bulls within the breed. All these traits were highly significant (P<0.01) and positively interrelated among each other in both the species (r= 0.277 to 0.925), except that the abnormal sperm per cent had negative correlations. These findings suggest that freezability of bull semen could be predicted fairly accurately on the basis of its initial quality and cold shock test.